Peran Sekolah Ekspor Dalam Meningkatkan Persentase Ekspor Indonesia Melalui Kegiatan Studi Independen - Dwi Syafitri; Tania, Ria; Perwira, Bintang; Yohana, Priski; Sukmawati, Dian (Papanda, 2023)
The research is used qualitative research method. This research aims to find out the role of export schools in increasing the percentage of Indonesian exports through independent study programs at the independent campus. This research is expected to be useful for increasing student competence in the field of exports so as to increase the percentage of exports and can be used as motivation with new learning models and techniques in academia. Because the export school has a very important role, namely as a facilitator and a place where students learn about how to export. So it is hoped that through this program, new Indonesian exporters will be born who are skilled at optimizing digital business in order to support the creation of 500 thousand new Indonesian exporters in 2030 as launched by the Indonesian Minister of Trade and the Indonesian Minister of Cooperatives and SMEs on February 17, 2021. Keywords: role of export school; export percentage; Study Independent Penelitian ini menggunakan metode penelitian kualitatif. Penelitian ini bertujuan untuk mengetahui peran sekolah ekspor dalam meningkatkan persentase ekspor Indonesia melalui program studi independen di kampus merdeka. Dan penelitian ini diharapkan dapat bermanfaat untuk meningkatkan kompentensi mahasiswadibidang ekspor sehingga dapat meningkatkan persentase ekspor serta dapat dijadikan motivasi dengan model dan teknik pembelajaran baru dalam bidang akademisi. Karena Sekolah ekspor memiliki peran sangat penting yaitu sebagai fasilitator dan wadah tempat mahasiswa mempelajari tentang bagaimana melakukan ekspor. Sehingga diharpkan melalui program ini akan lahir eksportir-eksportir baru Indonesia yang terampil mengoptimalkan digital business dalam rangka mendukung tercetaknya 500 ribu eksportir baru Indonesia pada tahun 2030 seperti yang dicanangkan oleh Menteri Perdagangan RI dan Menteri Koperasi dan UKM RI pada 17 Februari 2021. Kata Kunci : peran sekolah ekspor; persentase ekspor; Studi Independen